2023
DOI: 10.1002/adsc.202201384
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective Decarboxylative Direct Formylation of Nitrogen Heterocycles (Azaindoles, Indoles, Pyrroles) and Anilines Utilizing Glyoxylic Acid

Abstract: A new method for formylation of nitrogen heterocycles overcoming the limitations of classical approaches using a cheap feedstock formylating agent especially under mild and neutral conditions is the subject of this current investigation. This work describes direct formylation of nitrogen heterocycles (azaindoles, indoles, pyrroles) and anilines using glyoxylic acid as the formyl source and K2S2O8 as the exclusive reagent. The key features include a general method for both C‐ and N‐formylation under neutral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Following the inferences of control experiments (scheme 3) and prior literature reports, [5,[21][22][23][24] we tried to establish a plausible reaction mechanism of our developed methodology (Scheme 4). The reaction proceeds with the condensation of glyoxylic acid (2) to 1 a followed by its decarboxylation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the inferences of control experiments (scheme 3) and prior literature reports, [5,[21][22][23][24] we tried to establish a plausible reaction mechanism of our developed methodology (Scheme 4). The reaction proceeds with the condensation of glyoxylic acid (2) to 1 a followed by its decarboxylation.…”
Section: Resultsmentioning
confidence: 99%
“…Laha et al also reported the generation of a similar condensation intermediate. [21] The decarboxylation of A was carried out by the sulfate radical anion (SO 4 À .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of an extra electron from adduct (69.5) by SO 4 *À followed by rearrangement of electrons in the system could result in the formation of 69.6 (Scheme 69). [33] 7. Miscellaneous…”
Section: Formylation Of Azaindolesmentioning
confidence: 99%